[tex]a) (-\frac{1}{2} )^{3} * (-\frac{1}{2} )^{4}*(\frac{1}{2} )^{-7}= -\frac{1}{2} ^{0}= -1[/tex]
b)
[tex](\frac{1}{10})^{8} * (\frac{1}{5} ) ^{8} : (\frac{1}{50}) ^{6} = \frac{1}{10^8} * \frac{1}{5^8} : \frac{1}{50^6} = \frac{1}{10^8} * \frac{1}{5^8} * 5^6 * 10^6 = \frac{1}{10^8} * \frac{1}{5^2} *10^6=\frac{1}{10^2} * \frac{1}{5^2} = 0,01 * 0,25 = \frac{1}{2500}[/tex]
c) ... = [tex]2^{-6} * (-2^{-7}) : 2^{-13} * 10^{-13}*2^{-13}=-1* 10^{-13}*2^{-13}=-20^{-13}[/tex]
dalej nie robie bo to jakies turbo zj***ne i spedzilem 30 minut nad tym. Niech ci bóg da mądrość byku B)
Szczegółowe wyjaśnienie: